Neuropeptide S Receptor Stimulation Excites Principal Neurons in Murine Basolateral Amygdala through a Calcium-Dependent Decrease in Membrane Potassium Conductance - Sion Park; Pia Flüthmann; Carla Wolany; Lena Goedecke; Hannah Maleen Spenner; Thomas Budde; Hans-Christian Pape; Kay Jüngling (MDPI AG, 2021)
Background: The neuropeptide S system, consisting of the 20 amino acid neuropeptide NPS and its G-protein-coupled receptor (GPCR) neuropeptide S receptor 1 (NPSR1), has been studied intensively in rodents. Although there is a lot of data retrieved from behavioral studies using pharmacology or genetic interventions, little is known about intracellular signaling cascades in neurons endogenously expressing the NPSR1. Methods: To elucidate possible G-protein-dependent signaling and effector systems, we performed whole-cell patch-clamp recordings on principal neurons of the anterior basolateral amygdala of mice. We used pharmacological interventions to characterize the NPSR1-mediated current induced by NPS application. Results: Application of NPS reliably evokes inward-directed currents in amygdalar neurons recorded in brain slice preparations of male and female mice. The NPSR1-mediated current had a reversal potential near the potassium reversal potential (EK) and was accompanied by an increase in membrane input resistance. GDP-β-S and BAPTA, but neither adenylyl cyclase inhibition nor 8-Br-cAMP, abolished the current. Intracellular tetraethylammonium or 4-aminopyridine reduced the NPS-evoked current. Conclusion: NPSR1 activation in amygdalar neurons inhibits voltage-gated potassium (K+) channels, most likely members of the delayed rectifier family. Intracellularly, Gαq signaling and calcium ions seem to be mandatory for the observed current and increased neuronal excitability.